(untitled) (Journal of Human Sciences, 2023)
The importance of this study is that it has come to address one of the most important topics for discussion at the national and international levels, since the globalization of crime imposed a special and exceptional legislative situation based on a state of reconciliation of domestic legislation with the international community’s criminal orientation. What is known as the globalization of the criminal text on the one hand and the reconciliation between the fight against crime and the enshrinement of human rights on the other. That is what made the reality of the globalization of the law. As a modern legislative pattern, the principle of criminal legality is held from the rank of absolute highness to the circle of jurisprudence and judicial debate, and a place for study and analysis. At the end of this study, we found that the globalization of crime had led to the need to globalize today’s criminal policy and that it had been a reason to the change in the features of the principle of legality in its substantive part has been characterized by decline, deterioration and fragmentation, which constitutes a real failure in the field of protection of rights . By contrast, it has contributed significantly to the development of criminal procedures, the globalization of procedural rules and the documentation of international cooperation, Coordination and consolidation of efforts to combat crime despite the relative reversal of respect for human rights during the application of certain procedures, particularly those relating to the right to private life.